SYSTEMATIC LITERATURE REVIEW: PENALARAN INDUKTIF DAN DEDUKTIF SISWA SD DALAM PEMBELAJARAN MATEMATIKA - Nurlaila Ramadhan; Indri Masti; Vanska Lidia; Yuki Wulan Azzahwa; Hafiziani Eka Putri (Uninus Journal of Mathematics Education and Science (UJMES), 2026)
This study aims to analyze the inductive and deductive reasoning abilities of elementary school students in mathematics learning. This research employed a Systematic Literature Review (SLR) method. Data collection was conducted through Google Scholar and Scopus using the Publish or Perish application, with inclusion and exclusion criteria based on relevant keywords and specified publication years. Article selection followed the PRISMA flow diagram. Based on the analysis of 12 selected articles, the findings indicate that students’ inductive and deductive reasoning abilities remain relatively low, particularly in understanding problems, connecting information, and constructing solution steps. Several factors influencing these abilities include teacher-centered learning, the dominance of procedural exercises, and low student engagement in learning activities. Furthermore, the implementation of contextual learning approaches, such as Project Based Learning and Indonesian Realistic Mathematics Education (PMRI), has been shown to improve students’ reasoning abilities in mathematics learning.